Usefulness of intraoperative sentinel node palpation in breast cancer: a cross-sectional study - Bonilla Sepúlveda, Oscar Alejandro (2022)
Objective: To determine the usefulness of intraoperative palpation and macroscopic characteristics of the sentinel lymph node in breast cancer in predicting its involvement on microscopic examination. Methods: Descriptive cross-sectional study with secondary analysis of a surgeon's personal registry between May 1, 2018, and October 31, 2020, at a referral center in Medellin, Colombia. Women with breast cancer without clinical axillary involvement taken to surgery for sentinel node biopsy were included. Demographic, clinical and paraclinical data were collected and analyzed using descriptive statistics. Results: Of 355 patients who underwent sentinel node biopsy for breast cancer, the sentinel node detection rate was 98.3 % (n= 347). A higher probability of being affected was found in patients who underwent mastectomy (ORa= 4.61; 95% CI: 1.07-19.81), when the consistency of the node was hard or semi-hard (ORa= 3.90; 95% CI: 2.00-7.62) and when the shape of the node was lobulated or irregular (ORa= 12.98; 95% CI: 2.10-80.19). In contrast, it was less likely to be affected when it had received neoadjuvant chemotherapy (ORa= 0.11; 95% CI: 0.02-0.57). Conclusion: The evaluation of macroscopic features during sentinel node technique for axillary staging can predict its involvement on microscopic examination.